BALAI PEMBINAAN DAN PELATIHAN KETERAMPILAN ANAK JALANAN DENGAN PENDEKATAN FLEKSIBILITAS ARSITEKTUR DI SURAKARTA - Gigih Herry Purwoko; Musyawaroh Musyawaroh; Maya Andria Nirawati (ARSITEKTURA, 2016)
Surakarta city as a big city in Central Java, which continues to grow can not be separated from the phenomenon of street children problem. As a city that wants to be a child-friendly city, the phenomenon of street children in the city is less serious attention to the lack of street children buildings or vocational training for the street children. For it is necessary to design a building that is capable of being marcusuar in the overcome of street children problem in the city. Architectural flexibility is the tendency of architectural objects to be changed, both in shape, size and structure, with the aim of being able to adjust to the needs of users, making it more effective and efficient. The method used is the method of approach architecture with the flexibility of the architecture. The result obtained is a design of a building that is destined for coaching for the psychological rehabilitation as well as a place for the vocational training for the street children in Surakarta, which could accommodate the needs of users in an effective and efficient approach architectural flexibility.